Layanan Bimbingan dan Konseling pada Masa Pandemi Covid-19 - Sofah, Rahmi (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2020)
With the Copid-19 pandemic situation, the implementation of guidance and counseling services in schools was carried out online. This is in accordance with the Minister of Education and Culture Circular Letter Number 4 of 2020 with the term learning from home. To realize guidance and counseling services during the Covid-9 pandemic, counseling teachers are required to use technology in carrying out their roles to carry out various counseling services according to student needs. The counseling teacher can use a variety of media and communication platforms that are familiar to students. Cyber Counseling is an alternative that can be carried out by counseling teachers or counselors in carrying out guidance and counseling services during the Covid-19 pandemic. With cyber counseling, counseling teachers can facilitate students to get basic services, responsive services, and individual planning.